Unveiling Wordsworth's Daffodils: A Semiotic Tapestry of Signs and Symbols - Sulistiawati Sulistiawati; Nur Hikmah; Muhammad Hasbi (GLENS: Global English Insights Journal, 2024)
This research aims to identify and analyze signs and symbols in William Wordsworth’s poem I Wandered Lonely as a Cloud. This study employs a descriptive qualitative research design through a semiotic approach to investigate the function of signs and symbols in poetic discourse. The data in this research was collected from Wordsworth’s. I Wandered Lonely as a Cloud as the primary data source, while the secondary data sources are books, articles, and other online sources that support the primary data. The obtained data were analyzed using Charles Sanders Peirce’s semiotic model, which consists of an icon, index, and symbol. The data analysis was conducted in three stages: classification, display, and verification. The result of this research shows that the poem employs various phrases, which can be categorized as icons, indexes, and symbols. The signs function to surpass linguistic barriers and convey significant insights about the human spirit and its connection to the natural world. These can also serve as a reminder that even the most basic words, when skillfully composed and infused with symbolic significance, can have a lasting effect on readers, encouraging them to delve into their feelings and establish a stronger bond with the world.